Pengaruh Model Pembelajaran Experiential Learning Terhadap Keterampilan Berpikir Kritis Siswa Pada Mata Pelajaran Sejarah Kebudayaan Islam - Ridho Akbar; Jasiah Jasiah (JOURNAL SAINS STUDENT RESEARCH, 2025)
Critical thinking can be defined as the process and ability used to understand concepts, apply, synthesize and evaluate information obtained or information produced. Not all information obtained can be used as knowledge that is believed to be true to guide action, and not always the information produced is correct information. Critical thinking is a higher order thinking skill and has been known to play a role in moral development, social development, mental development and cognitive development. The author's aim is to find out whether there is an increase in students' critical thinking skills who are taught using the problem-based learning model (experiential learning). In the context of Islamic education, the learning media used must be in accordance with Islamic values ​​and can provide real experiences to students. This author aims to describe the application of an experience-based learning model (experiential learning), using quantitative methods with the subject of improving students' critical thinking skills in class XI Islamic cultural history subjects at MA Darul Ulum Palangka Raya.